2016
DOI: 10.1093/gerona/glw119
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Blood Cadmium Levels With Depression and Lower Handgrip Strength in a Community-Dwelling Elderly Population: A Repeated-Measures Panel Study

Abstract: After adjusting for potential confounders, blood cadmium concentrations were associated with depression and lower handgrip strength in an elderly population. The participants' depressive status partially mediated the association between cadmium levels and handgrip strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…The Q matrix was adapted from the analysis results obtained from Structure 2.2. The K matrix (kinship matrix) was obtained from the results of the relatedness analysis using SPAGeDi (Hardy and Vekemans, 2002 ). According to the correction method published by Benjamini and Hochberg ( 1995 ), a false discovery rate (FDR) of 0.05 was used as a threshold for significant associations.…”
Section: Methodsmentioning
confidence: 99%
“…The Q matrix was adapted from the analysis results obtained from Structure 2.2. The K matrix (kinship matrix) was obtained from the results of the relatedness analysis using SPAGeDi (Hardy and Vekemans, 2002 ). According to the correction method published by Benjamini and Hochberg ( 1995 ), a false discovery rate (FDR) of 0.05 was used as a threshold for significant associations.…”
Section: Methodsmentioning
confidence: 99%
“…Korea is one of the fastest aging developed countries, and previous studies focusing on older adults in Korea have demonstrated significant relationships of handgrip strength with metabolic syndrome, osteoporosis, fracture, cognitive impairment, and depression [11,26,27,28]. However, little is known about the prospective relationship between handgrip strength and all-cause mortality in middle aged and older Korean adults.…”
Section: Introductionmentioning
confidence: 99%
“…Out of 473 records identi ed during the database search and 21 additional records identi ed after reference list search, a total of 16 entries [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] were included in the study. The ow-chart of the search process is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The strongest points proved to be the Representativeness of the sampleonly Laredo-Aguilera et al [27] did not receive a point, and the Based on design and analysis -Seino et al [29] and Olgun Yazar & Yazar [34] received 1 out of 2 points. [22] and Hand Grip Meter 6103, Tanita (1 study) [28] hand dynamometers. Three studies failed to include the names of the dynamometer models.…”
Section: Resultsmentioning
confidence: 99%